Aggregation Behavior of a Six‐Membered Cyclic Frustrated Phosphane/Borane Lewis Pair: Formation of a Supramolecular Cyclooctameric Macrocyclic Ring System. (12th December 2018) - Jie, Xiaoming; Daniliuc, Constantin G.; Knitsch, Robert; Hansen, Michael Ryan; Eckert, Hellmut; Ehlert, Sebastian; Grimme, Stefan; Kehr, Gerald; Erker, Gerhard
Abstract: A new six‐membered cyclic frustrated phosphane/borane Lewis pair was liberated from its HB(C6 F5 )2 adduct by treatment with vinylcyclohexane. The system is an active frustrated Lewis pair that undergoes cycloaddition reactions with suitable π reagents and it splits dihydrogen. At room temperature in solution the new compound is a monomer, however, in the crystal and in solution at low temperature it aggregates to a thermodynamically favoured supramolecular macrocyclic cyclooctamer.